Wage growth in the civilian careers of military retirees - Loughran, David S., 1969-; Rand eBooks (Santa Monica, CA : RAND, 2002)
More than 20,000 individuals retire each year from the United States military who are eligible to receive a guaranteed annuity amounting to half or more of their basic military pay. Separating from the military at an average age of 43, the overwhelming majority of these retirees enter second careers in the civilian sector. This book addresses three important questions about the civilian labor market experience of military retirees: How do the wages of military retirees upon separation compare with those of comparably experienced and educated civilians? Do military retirees enjoy higher relative wage growth over their second careers than their civilian peers? Is the transition to civilian employment a difficult process for military retirees? The author finds that military retirees earn substantially lower wages than their civilian peers upon entering the civilian labor market and, moreover, the wages of military retirees remain low relative to civilian wages even as retirees gain civilian labor market experience.
"National Defense Research Institute."
"This study ... was prepared within the Forces and Resources Policy Center of RAND's National Defense Research Institute"--Preface.
Includes bibliographical references (p. 57-60).
Also available on the internet via WWW in PDF format.
Keywords: Military pensions -- United States; Retired military personnel -- Employment -- United States; Retired military personnel -- Salaries, etc. -- United States; Electronic books